Conceptual Approaches to Modeling the Learning Process and Development of Motor Abilities in Children and Adolescents - Худолій, О. М.; Іващенко, О. В. (Physical Education Theory and Methodology, 2013)
Research aim — to ground conception of construction of process of educating and developing motive flairs for children and teenagers on the basis of design of separate components of educational process. For the decision of the put tasks such methods of research : are in-process used design, approach of the systems, methods of theoretical analysis and generalization for the exposure of essence, leading tendencies of optimization of educational process and determination of theoretical pre-conditions and methodological approaches of his further improvement; pedagogical testing, methods of registration of sensomotor reactions, methods of registration of the state of the cardiovascular system, supervisions and pedagogical experiment for determination of model descriptions of children and teenagers, modes of the training loading; methods of mathematical analysis (logistic and asymptotic to the function) for determination of conformities to law of placing of facilities of primary orientation in the period of developing motive flairs, educating to physical exercises and undercooking to the competitions; mathematical methods of planning of multivariable experiments for the study of conformities to law of developing motive flairs, process of educating and preparation to the competitions. The got experimental material was subject to statistical treatment with the use of application of the statistical processing of data (MS Excel, Statistika 6.0) packages. Research results. It is set that on the basis of models of motive preparedness of children and teenagers the selection of basic, tricking into and preparatory exercises, and also stage control, comes true after the level of motive preparedness. On the basis of models of the training loading determined: size and orientation of loading; correlation of facilities of physical and technical preparation; terms of the use of loading of different orientation; terms for development of force and increase of capacity; terms of operative and current control. On the basis of models of process educating is determined: terms for educating by ability to manage motions, educating to physical exercises; order of decision of tasks of educating and selection of educational tasks; fundamental discipling to programming of educational process of children and teenagers; terms of operative and current control. Keywords: design, educating, motive capabilities, children, teenagers.